Goalkeeping in the soccer penalty kick - It is time we take affordance-based control seriously! - van der Kamp, J.; Dicks, M.; Navia, J. A.; Noël, B. (German Journal of Exercise and Sport Research, 2018)
The goalkeeper`s difficulty in the soccer penalty kick originates from the extreme spatiotemporal constraints of the situation. The present review claims that the current understanding is biased toward attributing a goalkeeper`s success in saving a penalty kick to perceptual-cognitive skill. To investigate the goalkeeper`s skill, researchers have often adopted video tasks. In doing so, they studied perceptual skill in isolation from action. We use affordance-based control theory to propose an alternative understanding and research methodology. We argue that goalkeepers in the penalty kick situation should regulate their actions in ways that sustain the perception of stoppability. To capture this, we outline the building blocks for a required lateral velocity model, in which the goalkeepers` required actions are scaled to their maximum capabilities. In doing so, we provide new directions for research. Die Schwierigkeiten für den Fußballtorhüter beim Strafstoß beruhen auf den extremen räumlich-zeitlichen Einschränkungen der Situation. In der vorliegenden Übersicht postulieren wir eine Verzerrung der aktuellen Deutung dahingehend, dass der Erfolg eines Torhüters beim Parieren eines Strafstoßes der perzeptorisch-kognitiven Fertigkeit zugeschrieben wird. Zur Untersuchung der Fertigkeit des Torhüters werden häufig Videoaufgaben genutzt. Auf diese Weise wird die perzeptorische Fertigkeit isoliert von der Handlung betrachtet. Ausgehend von der Theorie der affordanzbasierten Kontrolle schlagen wir eine alternative Deutung und Forschungsmethodik vor. Wir argumentieren, dass Torhüter in der Strafstoßsituation ihre Handlungen so steuern sollten, dass die Wahrnehmung der Haltbarkeit aufrechterhalten bleibt. Zur Erfassung umreißen wir die Bausteine eines Modells der erforderlichen lateralen Geschwindigkeit, in dem die erforderlichen Handlungen der Torhüter auf ihr maximales Leistungsvermögen skaliert sind. Damit werden neue Forschungsimpulse gesetzt.